Pengaruh Empowering Leadership, Training, Dan Work Engagement Terhadap Employee Performance Dimoderasi Oleh Role Of Ambiguity (Studi Pada Badan Kepegawaian Negara Pusat ) - Vicky Ayu Efrilia; Tantri Yanuar Rahmat Syah (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
A number of previous studies have mentioned that Employee Performance is one of the important factors that determine the success of an organization. The purpose of this study was to test the relationship of Empowering Leadership, Training, and Work Engagement to Employee Performance moderated by the Role of Ambiguity in the Central State Staffing Agency. As an initial sample, questionnaires were distributed to 30 employees of the Central State Staffing Agency to test the series of hypotheses in this study where the questionnaire contained 51 questions, then changed to 34 questions on the basis of relevance. The data analysis method used in this study is Structural Equation Modelling (SEM) listrel by distributing questionnaires to 350 staff at the Central State Staffing Agency. Of the entire questionnaire, a total of 310 were filled out and can be used for further research analysis purposes.